TRIGONOMETRIYALIQ TEŃLEMELER DÚZIWDE QATNASATUǴIN AŃLATPALAR HÁM OLARDI TÚRLENDIRIW USILLARI - Izetaeva, G.; Djanxodjaev, N.; Erejepova, V.; Kewnimjaeva, F. (SCIENCE and SOCIETY, 2022)
This article discusses, more widely studied expressions involved in the construction of trigonometric equations, and methods for their interpretation.